Marketing and Regional Integration for Food Security in the Arab World. (June 2019) - Bagnied, Mohsen A.; Speece, Mark
The Middle East / North Africa (MENA) region faces serious food insecurity, with an increasing gap between food production and consumption. Using resource advantage theory from macromarketing, we demonstrate that the agriculture / agribusiness industry would be highly competitive with economic integration of the Nile Valley (Egypt and Sudan) with the Arab Gulf countries. Individually, these sub-regions have critical disadvantages, but as a bloc, complementary strengths could make the industry quite competitive. Of course, integration within MENA has been discussed for decades, although usually as a political concept, which is unlikely to succeed in the foreseeable future. From a macromarketing perspective, economic integration is quite viable, and very beneficial to food security in the region.